Model-based analysis of coupled equilibrium-kinetic processes: indirect kinetic studies of thermodynamic parameters using the dynamic data1. Issue 9 (7th May 2015) - Emami, Fereshteh; Maeder, Marcel; Abdollahi, Hamid
<x xml:space="preserve">Abstract</x> Schematic of intertwined equilibrium-kinetic model at time = 0, 1, 2…T when both equilibrium and kinetic models are solved explicitly.